Holding Space in these Uncertain Times - Risk, Laura (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
âpihtawikosisâniskwêw artist Moe Clark is a nomadic songbird with wings woven from circle singing and spoken word. Originally from Treaty 7, she has called tio'tia:ke (Montreal) home for over a decade. In this interview, she speaks with Laura Risk about continuing to create music and build community during the COVID-19 pandemic.